Inclusion Education: Learning Reading Arabic Language And Alquran For Blind - Rubini Rubini; Cahya Edi Setyawan (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2019)
Inclusive education is one of the priorities that must be considered for the sake of equality in educating the nation. Inclusive education is contained in the form of learning towards a group of people with special needs. Special needs in Indonesia are mostly those who have physical disabilities, one of the blind. This study aims to determine how the stages of learning to read Arabic letters and the Qur'an for the blind. This type of research is library research, with the method of collecting data, searching, analyzing, and synthesizing the latest research. The results of the study stages of learning to read Arabic letters and the Qur'an for the blind are: memorize Arabic Braille numeric codes from Alif أ to Ya ي, memorizing Arabic punctuation, practice fingering Braille hijaiyah letters and Arabic punctuation, IQRA reading practice starting from words to simple sentences, and practice reading the Koran which starts from short letters to long letters.